Modeling Trade Openness and Life Expectancy in China - Imran Shah M; Ullah I; Xingjian X; Haipeng H; Rehman A; Zeeshan M; Alam Afridi FE (Dove Medical Press, 2021)
Muhammad Imran Shah,1 Irfan Ullah,2 Xiao Xingjian,2 Huang Haipeng,2 Alam Rehman,3 Muhammad Zeeshan,4 Fakhr E Alam Afridi5 1School of Mathematics and Statistics, Wuhan University, Wuhan, People’s Republic of China; 2Reading Academy, Nanjing University of Information Science and Technology, Nanjing, People’s Republic of China; 3Faculty of Management Sciences, National University of Modern Languages Islamabad, Islamabad, Pakistan; 4College of Business Administration, Liaoning Technical University, XingCheng, Liaoning Province, 125105, People’s Republic of China; 5Islamia College Peshawar, Peshawar, PakistanCorrespondence: Irfan UllahReading Academy, Nanjing University of Information Science and Technology, People’s Republic of ChinaEmail irfnecon@nuist.edu.cnObjective: This study investigates life expectancy and trade openness in China for the period 1960– 2018.Methods: We purposed a theoretical model that is tested for China by applying regime-switching regression.Results: Our findings suggest that trade openness increases life expectancy in China; trade affects life expectancy from two aspects; firstly, trade expansion and industrialization lead to high economic activities and resulted in raise the income of the people in society leading to improve life expectancy. Secondly, industrial expansion increases the CO2 emissions which leads to imposes a negative implication on human health and thus reduces life expectancy.Conclusion: Thus, the net effect of trade liberalization depends on the value of income effect and volume of CO2 emissions. Therefore, the government needs to support the trade policies which causes a low level of CO2 emissions, the government may provide incentives to exports and industrialists to adopted green energy in the production process. Besides, the government may impose some regulations such as carbon tax to mitigate the CO2 emissions in society.Keywords: trade, life expectancy, CO2 emissions, health quality, regime-switching regression, China